Developments in The Field of Muamalah, Banking Economics, and Contemporary Finance - Abdullah Ahadish Shamad Muis; Muh. Arief Budiman; Abdul Majid Toyyibi; Nur Rif’ah Syahirah Binti Haji Muhammad Kamal Shahrum (Ad-dawl : Jurnal Islamic Studies, 2025)
This study aims to analyze the development of contemporary Islamic law in the field of economic muamalah, particularly in the practices of Islamic insurance (takaful), the Ijarah al-Muntahiya bi al-Tamlik (IMBT) contract, and Islamic credit cards, from the perspective of maqashid shariah and maslahah mursalah. This research employs a qualitative approach using the library research method, focusing on conceptual and comparative analysis of classical and contemporary sources, such as fiqh books, fatwas from the National Sharia Council–Indonesian Ulema Council (DSN-MUI), and related academic literature. The results show that the development of the modern economy demands flexibility in Islamic law through contextual ijtihad based on maqashid shariah and maslahah mursalah. Islamic insurance is viewed as a form of financial protection that aligns with the principle of mutual assistance (ta’awun), grounded in DSN-MUI fatwas that permit its practice as long as it meets sharia requirements. The IMBT contract represents an innovation in lease-to-own financing, combining the principles of ijarah and bai’ legitimately as long as it does not involve elements of riba (usury). Meanwhile, Islamic credit cards are built upon a combination of kafalah, qardh, and ijarah contracts, serving as an adaptation to modern transaction needs without abandoning the principles of justice and transparency.